Penerapan Model State Capitalism sebagai Strategi Pembangunan Ekonomi Singapura - Jenifer (Jurnal Sentris, 2024)
Since its independence, Singapore has transformed from a developing country into one of the most economically developed ones by implementing state capitalism. State capitalism adopts liberalism and mercantilism to intensify the supervision of government in the midst of economic liberalization. This intrigues further question in regards how Singapore is able to find the common ground between state and business actors' interest through the creation of State Owned Enterprises (SOEs) and how the government execute its involvement, this article focuses on the implementation of state capitalism and its impacts on the companies and vital industries’ development. This article analyses the implementation of state capitalism in three periods: pre state capitalism, after independence, and after crisis (1998-2022) Keywords: state capitalism; State Owned Enterprises; Government Linked Companies